1997
DOI: 10.2337/diacare.20.5.867
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes: Should It Be Added to the Syndrome of Insulin Resistance?

Abstract: Our results show that many of the known metabolic components of the syndrome of insulin resistance (syndrome X) are predictive of GDM. These results are in keeping with the argument that GDM is one phase of the syndrome of insulin resistance. We suggest that GDM be looked upon as a component of the syndrome of insulin resistance that provides an excellent model for the study and prevention of NIDDM in a relatively young age-group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
59
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 10 publications
5
59
0
Order By: Relevance
“…Although gestational diabetes shares many features of the insulin resistance syndrome [49], no change was observed in plasma leptin following oral glucose loading despite increased insulin secretion in this study as well as by others [50,51]. Noteworthy is the impaired stimulated insulin secretion for prevailing insulin sensitivity despite post-prandial hyperglycaemia compared to normal glucose tolerance.…”
Section: Discussionmentioning
confidence: 41%
“…Although gestational diabetes shares many features of the insulin resistance syndrome [49], no change was observed in plasma leptin following oral glucose loading despite increased insulin secretion in this study as well as by others [50,51]. Noteworthy is the impaired stimulated insulin secretion for prevailing insulin sensitivity despite post-prandial hyperglycaemia compared to normal glucose tolerance.…”
Section: Discussionmentioning
confidence: 41%
“…In this context, it is possible that increased insulin sensitivity prior to pregnancy may enable better maintenance of insulin sensitivity in late pregnancy, thereby allowing for appropriate beta-cell compensation and the maintenance of normoglycemia. Such an effect may be particularly important in women at risk of GDM, since this patient population exhibits chronic insulin resistance that is believed to pre-date pregnancy (31,32). Indeed, as increased insulin resistance in 1 st trimester (which largely reflects the pre-gravid state) predicts a higher risk of developing GDM later in pregnancy (33,34), it is plausible that improving insulin sensitivity prior to pregnancy would reduce GDM risk.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, GDM has even been proposed to be a component of the metabolic syndrome (Clark et al 1997). In their study, Clark et al (1997) showed that, at the time of their antepartum OGTT, women with GDM expressed markers of the metabolic syndrome, including low serum HDL cholesterol and higher fasting plasma insulin, triglycerides, free fatty acids and pre-pregnancy BMI. These common features of the metabolic syndrome were each individually predictive of GDM, and persisted after adjustment for differences in BMI (Clark et al, 1997).…”
Section: Prediction Of Gdm By Metabolic Syndrome Components In Early mentioning
confidence: 99%
“…In their study, Clark et al (1997) showed that, at the time of their antepartum OGTT, women with GDM expressed markers of the metabolic syndrome, including low serum HDL cholesterol and higher fasting plasma insulin, triglycerides, free fatty acids and pre-pregnancy BMI. These common features of the metabolic syndrome were each individually predictive of GDM, and persisted after adjustment for differences in BMI (Clark et al, 1997). In addition to conventional measures of metabolic syndrome, several non-traditional biomarkers have also emerged as possible predictors of GDM.…”
Section: Prediction Of Gdm By Metabolic Syndrome Components In Early mentioning
confidence: 99%